Severe Juvenile Open Angle Glaukoma in A Teenager: A Case Report - Baihaqi, Nadya Divina; Agustanti, Rika; Noerdiyani, Niken Indah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Juvenile open-angle glaucoma (JOAG) is a rare but severe form of glaucoma affecting individuals between the ages of 3 and 40. While it shares pathophysiological features with primary open-angle glaucoma (POAG), JOAG often progresses more rapidly and is associated with higher intraocular pressure (IOP) at diagnosis. Genetic mutations, such as in the MYOC and OPTN genes, are common in JOAG, though family history may not always be present. Early diagnosis and intervention are crucial to prevent permanent vision loss. A 15-year-old girl presented with blurry vision and frequent headaches, which had progressively worsened over two years. She experienced sudden loss of vision in the left eye a year prior and episodes of tunnel vision. She had no family history of glaucoma. Examination revealed visual acuity of 6/15 in the right eye and no light perception in the left. IOP was 23 mmHg in the right eye and 18.3 mmHg in the left, despite treatment with Timolol and Latanoprost. Optic nerve examination showed advanced glaucomatous optic neuropathy (GON), with a cup-to-disc ratio of 0.9 in the right eye and 1.0 in the left. Humphrey perimetry revealed severe visual field defects, and optical coherence tomography (OCT) showed significant retinal nerve fiber layer (RNFL) thinning in both eyes. Despite medical therapy, her condition continued to deteriorate, indicating a need for surgical intervention to better control IOP and prevent further vision loss. Gonioscopy confirmed open anterior chamber angles, consistent with JOAG. This case underscores the importance of early detection and aggressive management in JOAG. Despite medical therapy, the patient exhibited significant optic nerve damage and visual field loss, necessitating surgical consideration. Given the rapid progression, early surgical intervention may offer better outcomes in controlling IOP and preserving vision. Long-term follow-up and comprehensive management are crucial to preventing further deterioration. Genetic testing may help clarify the etiology, particularly in cases with no family history.